2015
DOI: 10.1186/s13018-014-0143-y
|View full text |Cite
|
Sign up to set email alerts
|

Additional bone graft accelerates healing of clavicle non-unions and improves long-term results after 8.9 years: a retrospective study

Abstract: BackgroundClavicle non-unions can occur after both conservative and operative treatment failure. Here, we investigated the outcome of patients with delayed fracture healing or non-unions of the clavicle. Patients underwent revision surgery by plate osteosynthesis of the clavicle with or without bone grafting. Our aim was to determine rates of bone healing and the functional long-term outcome.MethodsThe study population of 58 consecutive patients was divided into group 1 (n = 25; no bone graft) and group 2 (n =… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
30
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(32 citation statements)
references
References 33 publications
0
30
0
Order By: Relevance
“…6 Neer described nonunion rates of 0.1% after conservative treatment and 4.4% after operative treatment. 1 Several factors predispose to nonunion of the clavicle like inadequate conservative treatment and immobilisation, severity of trauma and fracture comminution 7,8 , re-fracture, distal-third fracture 1,9 , marked displacement or shortening of >2 cms, soft-tissue interposition, and primary open reduction. 10,11 Nonunion can be either atrophic or hypertrophic type.…”
mentioning
confidence: 99%
See 3 more Smart Citations
“…6 Neer described nonunion rates of 0.1% after conservative treatment and 4.4% after operative treatment. 1 Several factors predispose to nonunion of the clavicle like inadequate conservative treatment and immobilisation, severity of trauma and fracture comminution 7,8 , re-fracture, distal-third fracture 1,9 , marked displacement or shortening of >2 cms, soft-tissue interposition, and primary open reduction. 10,11 Nonunion can be either atrophic or hypertrophic type.…”
mentioning
confidence: 99%
“…5,6,7,16,17,18,19,20, Advantages over intramedullary fixation are improved rotational stability, ability to incorporate an intercalary graft and no fear of implant migration. 21 Few authors did not find the need of bone grafts from the iliac crest and suggested plating alone, 22,23 especially in hypertrophic types of nonunions 7,24 and well-vascularised bone beds after local preparation. 7 Bone grafts will hasten bone healing when nonunion clavicle is treated with plating and bone graft.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Finally, the construct must be completely coated with the reinsertion of the muscles. Schnetzke et al (35) have shown that an additional clavicle bone graft accelerates healing of non-unions and improves long-term results after 8.9 years of follow-up. Furthermore, the autologous bone grafting was performed to provide the length of the segment.…”
mentioning
confidence: 99%